Formation kinetic study of thermally induced trans and conjugated linoleic acids in corn oil - Hu, Yumeng; He, Fan; Liang, Manzhu; Li, Zhenyuan; Huang, Xuegang; Hu, Hui; Gu, Fengying; Wang, Qiang; Guo, Qin (Frontiers in Food Science and Technology, 2025)
BackgroundCorn oil, known for its high linoleic acid (LA) content, is vulnerable to isomerization during thermal processing. This results in the production of harmful trans-linoleic acid isomers (TLAs) and small amounts of beneficial conjugated linoleic isomers (CLAs).MethodsThis study examined the change in formation of TLAs and CLAs in corn oil heated to temperatures between 180°C and 240°C, and studied the kinetics of their formation, utilizing infrared spectroscopy and gas chromatography to clarify the reaction’s rate-determining steps and underlying mechanisms.ResultsThe results indicated the predominant generation of three distinct TLA and CLA isomers, with their levels showing a positive correlation with both the temperature and duration of heating. Importantly, the formation of mono-TLA isomers emerged as the rate-controlling step in the isomerization process, while the presence of O2 accelerated the formation of both TLA and CLA isomers. This study provided mechanistic insights and predictive models for forming TLA and CLA isomers under aerobic and anaerobic conditions.ConclusionThese findings imply that modulating the synthesis of mono-TLA isomers could serve as an effective strategy for reducing TLA formation and enhancing the conversion of TLA to CLAs in heated corn oil, thereby establishing a theoretical framework for precisely regulating TLAs.